Classroom Teachers' Efforts to Improve Students' Discipline in Collecting Assignments in Cluster 6 of Kepanjen Sub-District - Sholikha, Anisyatus; Suhartono, Suhartono (Journal of Education for Sustainability and Diversity, 2024)
Please The purpose of discipline is to shape behavior in such a way that students will fit the roles set by the cultural group with which the individual is identified. Discipline applied in schools certainly cannot escape the role of a teacher, depending on how the teacher treats students. The purpose of this research is to describe the class teacher's efforts to improve the discipline of students in collecting assignments. This study uses a descriptive quantitative research method. The research location will be conducted in Cluster 6 Kepanjen District which consists of 6 schools namely Panggungrejo 4 Kepanjen Elementary School, Kepanjen 3 Elementary School, Kepanjen 2 Elementary School, Penarukan Elementary School, Salsabila Kepanjen Elementary School, Wahidiyah Kepanjen Elementary School. While the technique of data collection was carried out by questionnaires and documentation with a proportionate stratified random sampling technique. The results showed that the teacher's efforts in the form of making rules did not make students' discipline in collecting assignments increase or decrease, the teacher's efforts in the form of giving punishments did not make students' discipline in collecting assignments increase or decrease, then the teacher's efforts in the form of giving good rewards in increasing student discipline in collection of assignments, and finally consistent teacher efforts also do not make students' discipline in collecting assignments increase or decrease.